The experiences of older persons living with chronic diseases in Ga-Dikgale, Limpopo Province - Tshishonga, Sedrose Ndivhuso (University of Limpopo, 2016)
The deterioration of health associated with chronic diseases such as hypertension and diabetes mellitus often leads to psychological problems especially among ageing older persons. The aim of the present study was to explore the lived experiences of older persons living with chronic diseases in Ga-Dikgale community in the Limpopo Province. Specifically, the study sought to determine the subjective meanings that older persons living with chronic diseases attach to their conditions; to establish older persons’ causal explanations of their chronic diseases; and, to determine the psychological strategies that older persons use to manage their conditions. A qualitative approach, and in particular, the phenomenological method was used in the present study. Ten older persons living with the experiences of chronic diseases (male = 3: female = 7), aged between 60 and 90 were selected through purposive sampling and requested to participate in the study. Data were collected using semistructured interviews and analyzed using the Interpretive Phenomenological Analysis (IPA) method. The themes that emerged from the study included the following: a). The subjective explanations by older persons living with a chronic disease; b). Manifestations of chronic diseases; c). The psychological coping strategies used by older persons; d) The management of chronic diseases. The findings of the present study further suggest that the participants understand their illnesses as chronic conditions that require long-term management. A number of psychological strategies are utilised by the participants to cope with their chronic conditions. These include passive/active coping and cognitive reappraisal coping strategies. With regard to the management of chronic conditions, most participants were of the view that medical treatment received from the clinic is appropriate for the treatment of their conditions. Some of the participants were however of the view that the nurses did not give them enough information about their chronic condition. The study is concluded by making a number of recommendations that among others include calling for more studies that should be conducted on the impact of chronic diseases on the family structure.
Thesis (M. A. (Psychology)) -- University of Limpopo, 2016
Keywords: Old aged persons; Chronic diseases; Diabetes; Hypertension; Health psychology; Chronic diseases